STATES’ TITLE TO TERRITORY IN REMOTE AREAS AND INDIGENOUS PEOPLES IN THE ARCTIC - Salinaitė, Birutė M.; Kirchner, Stefan (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2016)
Annotation: Until recently, indigenous peoples were ignored in international law. In recent decades, their legal status has significantly improved, although the full scope of their rights is still being discussed. Remote areas which have been home to indigenous peoples have long been misunderstood as being terra nullius, that is, open for acquisition – a view which has only changed in the last century. The acquisition of territory without regard for the local population is no longer compatible with international law. Statehood requires not only a territory and a people but also the effective exercise of public authority. Such exercise of authority can play a role – if it is legitimate – in the establishment of a legal title to a territory. In remote and sparsely settled areas, it can be argued that the level of authority which is to be exercised may be lower than elsewhere. It might be sufficient for a state to simply have a better title to a territory than an other state in order to establish a legal title. Yet, this does not mean that the local population, which is the original holder of the title, can be ignored because they, too, have a status under international law.